Integrasi Data Envelopment Analysis dan Analisis Rasio Keuangan untuk Penilaian Efisiensi Perusahaan IDXBUMN20 - Astuti, Tutut Dewi; Maruddani, Di Asih I (Jurnal Kajian Akuntansi, 2024)
Corporate efficiency is a critical indicator for assessing the performance of state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX). In the era of global competition, SOEs are required to optimize resources to achieve sustainable financial performance. One of the widely applied approaches for measuring relative efficiency among firms is Data Envelopment Analysis (DEA), which can be integrated with financial ratio analysis to provide a comprehensive assessment. This study aims to evaluate the efficiency of IDX BUMN20 companies by integrating DEA and financial ratio analysis. The input variables consist of Debt to Equity Ratio (DER), Price Earning Ratio (PER), and stock return volatility, while the output variables include Return on Assets (ROA), Return on Equity (ROE), Price to Book Value (PBV), Dividend Yield (DY), and Earnings per Share (EPS). The DEA CCR model was employed to estimate the efficiency scores of each company. The findings indicate that several firms such as PTBA, BMRI, BJBR, AGRO, and TLKM achieved an efficiency score of 1.00, suggesting full efficiency. In contrast, companies such as SMGR and BBNI recorded scores below 0.40, indicating significant inefficiency. This study concludes that DEA combined with financial ratio analysis serves as an effective tool for performance evaluation and provides managerial insights for improving efficiency in underperforming companies.